2021
DOI: 10.1002/ase.2142
|View full text |Cite
|
Sign up to set email alerts
|

Technological resources for teaching and learning about human anatomy in the medical course: Systematic review of literature

Abstract: The consolidation of technology as an alternative strategy to cadaveric dissection for teaching anatomy in medical courses was accelerated by the recent Covid‐19 pandemic, which caused the need for social distance policies and the closure of laboratories and classrooms. Consequently, new technologies were created, and those already been developed started to be better explored. However, information about many of these instruments and resources is not available to anatomy teachers. This systematic review present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 143 publications
0
24
0
Order By: Relevance
“…Dissection of cadavers has remained the “gold standard” in teaching anatomy at medical universities for decades 1‐3 ; however, today there is a lack of anthropomorphic models for both graduate and postgraduate students which has led anatomy educators to turn to new teaching modalities 4‐7 . In addition, the growing curricular volume of medical universities and reduction of hours dedicated to anatomy courses often requires less time‐consuming teaching methods than dissection 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissection of cadavers has remained the “gold standard” in teaching anatomy at medical universities for decades 1‐3 ; however, today there is a lack of anthropomorphic models for both graduate and postgraduate students which has led anatomy educators to turn to new teaching modalities 4‐7 . In addition, the growing curricular volume of medical universities and reduction of hours dedicated to anatomy courses often requires less time‐consuming teaching methods than dissection 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Dissection of cadavers has remained the "gold standard" in teaching anatomy at medical universities for decades [1][2][3] ; however, today there is a lack of anthropomorphic models for both graduate and postgraduate students which has led anatomy educators to turn to new teaching modalities. [4][5][6][7] In addition, the growing curricular volume of medical universities and reduction of hours dedicated to anatomy courses often requires less time-consuming teaching methods than dissection. 8,9 In parallel, computer-assisted learning (CAL) technologies, such as virtual reality (VR), [10][11][12][13] and augmented reality (AR), 14 three-dimensional (3D) models, [15][16][17] and interactive anatomical atlases [18][19][20] have rapidly advanced and grown in popularity.…”
Section: Introductionmentioning
confidence: 99%
“…We read, with great interest, the review article recently published in the Anatomical Sciences Education by Santos et al ( 2022 ), who explored and synthesized the technological resources used to teach anatomy. Recent randomized studies have demonstrated the significant importance of new innovations in anatomy courses as they can increase student satisfaction, involvement, and knowledge acquisition (Guze, 2015 ; Gloy et al, 2022 ).…”
mentioning
confidence: 99%
“…To the Editor, Anatomical Sciences Education It was our pleasure to read the interesting systematic review by Santos et al 1 about the use of technological resources in medical anatomy education. It was concluded that there was a neutral or beneficial result in the use of technology associated with traditional anatomy teaching modalities.…”
mentioning
confidence: 99%
“…We would like to note that differentiation of the outcomes which concern cadaveric dissection is necessary. As it was pointed out by Santos et al, 1 traditional anatomy education is based on cadaveric dissection.…”
mentioning
confidence: 99%